The language of defamation cases - Shuy, Roger W. (New York ; Oxford : Oxford University Press, 2010)
Slander and libel cases are largely about how one party uses language in ways that are claimed to defame one another. Linguistic expertise can be central to the case. Here, Shuy describes 11 representative lawsuits for which he served as a consultant.
Includes bibliographical references and index.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Libel and slander -- United States